2021
DOI: 10.1186/s12905-021-01480-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and emotional well-being in premenopausal and postmenopausal women: a cross-sectional cohort study

Abstract: Background Menopause, the absence of ovarian sex steroids, is frequently accompanied by emotional and physiological changes in a woman´s body, as well as oral health changes. The present study aimed to evaluate the association between the periodontal health status and emotional and physical well-being among postmenopausal women (PMW) in comparison with regularly menstruating premenopausal women (RMPW). Methods A total of 115 women (PMW, n = 56, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 51 publications
(57 reference statements)
2
32
0
Order By: Relevance
“…Similar to the present study, Yakar et al [ 32 ] showed that events with hormonal changes were not associated with periodontitis and the presence of a depressive mood in different periods in a women's lifetime could be a risk factor for periodontitis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to the present study, Yakar et al [ 32 ] showed that events with hormonal changes were not associated with periodontitis and the presence of a depressive mood in different periods in a women's lifetime could be a risk factor for periodontitis.…”
Section: Discussionsupporting
confidence: 89%
“…We were not able to find any other epidemiological population-based studies on the relationship between the history of endogenous hormonal fluctuations and periodontitis except two studies by Yakar et al [ 32 ] and Romandi et al [ 24 ] Romandi et al showed periodontitis was directly associated with a longer duration of breastfeeding and was inversely associated with artificial menopause and early and late menopausal ages. The difference between the present study and Romandi et al's study can be due to differences in race, group classification, sample size, and the use of different models.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Increased dental plaque levels may lead to an inflammatory breakdown of the periodontal tissues, and vice-versa, systemic inflammation induced by the presence of periodontitis may lead to depression [ 84 , 85 ]. A study by Yakar et al confirmed there is an association between the number of missing teeth, poor emotional well-being, and menopause [ 86 ]. However, due to the fact that both depression and periodontitis are chronic in nature, further research in this field should be carried out to assess their patterns of progression and mutual correlations during menopause.…”
Section: Periodontal Disease In Menopausal Womenmentioning
confidence: 99%